Economic hardship, family support and subjective wellbeing among vulnerable-to-poverty household heads in Selangor, Malaysia - Ismail, Noraini (2016)
Well being (WB) has been studied by social scientists for decades. Little attention was given to subjective approach of WB among household heads (HHHs) that are vulnerable to poverty (VTP). This study adds to the existing literature on subjective well being (SWB) of people who are VTP in Malaysia. People differ in their experiences of SWB. Some individuals experience low levels of SWB even with certain advantages. There are evidence to suggest that poor people does not necessarily have low levels of SWB. It is thought that there is a strong link between income, utility and WB. However, some studies indicate that income, poverty and various hardship measures are only moderately interrelated. Available research indicates that people are able to evaluate their own SWB. Other things can make people well. There are some evidence to suggest that non-poor people are more likely to report varying degrees of hardship than poor people. Past literatures showed that there are several determinants like socio-demographic, socio-economic and social capital are identified as dynamics for quality of life in Malaysia and it is found that very few studies on WB are conducted in Malaysia either using objective or subjective measures. This study is therefore one of the first, if not the first, to truly enhance the comprehension of the SWB of VTP HHHs in Malaysia. The objectives of the study are: i) to assess the level of SWB among vulnerable HHHs; ii) to describe the level of economic hardship (EH) experienced by VTP HHHs; iii) to determine the level of family support (FS) of the VTP HHHs; iv) to identify the relationship between EH and SWB; and v) to examine the moderating effects of FS on the relationship between EH and SWB. The respondents are 379 VTP HHHs in selected districts of Selangor, Malaysia. The study is based on a data collected in 2010, which uses the “Vulnerability Index” instrument that was designed for the research of Vulnerability Index, by a group of researchers in the Faculty of Human Ecology, Universiti Putra Malaysia. The Structural Equation Modelling (SEM) AMOS including The Confirmatory Factor Analysis, The Measurement Model, The Structural Model, and the Multi Group Analysis were employed to examine the levels of SWB, EH and FS, correlation between EH and SWB, as well as the moderation effect of FS on the relationship between EH and SWB. The findings of the study have theoretical, practical and methodological implications. The data shows 91.8% of HHHs were satisfied with their lives. HHHS have stable levels of SWB which strengthen the Set Point Theory. Data shows 91.3% of HHHs have experienced some EH, HHHs can accommodate EH. The finding fits the Theorem of Incomparable Utilities. Data shows 90.7% HHH have received the support from family. Family plays an important role as resources which provide support to the HHHs. The result is in line with the Social Production Function Theory. Practically this study contributed in terms of actions projected as interventions aimed in enhancing SWB among VTP populations. The study contributed methodologically in terms of using SEM AMOS, whereas previous studies used SPSS. This study is exceptional since it uses indirect measures of material hardship to identify individuals who do not consume minimal levels of basic goods and utilities. For the hypotheses testing, the study discovered that the EH had a significant negative relationship with SWB. The level of FS has not significantly affected SWB. The hypothesized measurement model of FS fully moderated the relationship between EH and SWB. The hypothesized structural model of EH and SWB fits the respondents’ data. The moderation effect of FS was more apparent among those who reported to have the most support from their families as compared to those who reported to have more and least support. Consistent with the Set-Point Theory, the level of SWB was firm although with the existence of EH. The findings of the study revealed the importance of FS in lessening the effect of EH on SWB. HHHs that were characterized as VTP are HHs that have these characteristics; either single parents and aged, or having disabled members in the HH. FS in terms of psychological and physical helps can enhance their SWB. The result supported the theory of Social Production Function where the HHH was presumed to have achieved their SWB by optimizing within their limited resources. The study analysis suggests a moderation effect of FS on the relationship between EH and SWB among VTP HHHs in Malaysia. FS buffers the relationship between EH and SWB. A novel result has not yet established in such a framework. Policy implications of the findings were discussed in the effort to promote SWB enhancement in the country. The outcome of the study also established the fact that individuals’ perspectives of their own SWB were unique and was sometimes not influenced by any sociological, psychological, economical or environmental complications.